Evaluation of Hybrid and OPV Maize Varieties for Grain Yield and Agronomic Attributes under Farmer's Field Conditions at Dukuchhap - Paudel, Min N. (Nepal Agriculture Research Journal, 2014)
Field experiments were conducted during two consecutive years 2006 and 2007 in full season of maize (May-Sep) at Dukuchhap, Lalitpur to find out impact of growing hybrid and OPV maize in different rows combinations with respect to their pure stands in same environment of growing and to sort out non-lodging maize varieties. The experiments consisted of an open pollinated variety (OPV) 'Deuti' and hybrid 'Gaurab' in different row combinations (50% hybrid + 50% OPV, 75% hybrid + 25% OPV, 75% OPV + 25% hybrid plus their pure stands). The results showed that Gaurab (yellow, flint type) and Deuti (white, semi- flint type, selected from CIMMYT's material ZM 621) did not vary significantly in grain yield and yield components. There was no effect of mixed row culture between the OPV and hybrid for grain yield and yield attributes. A bivariate correlation coefficient between agronomic traits and ear traits indicated that there was a positive relation among these traits. However, a positive and highly significant (r = 0.766**) relationship between ear fill and ear length was observed while a very weak relation (r = 0.096*) between grain weight/ear and ear height was also noticed suggesting taller the ear height lower the grain yield/ear and vice versa. The findings of the study support that plant height and ear height were weakly related with other ear traits; nevertheless, these were highly related to grain weight/per plant. To cope with stalk lodging problem and to attain higher grain yield these varieties are equally potential and recommended to grow under Dukuchhap conditions.Nepal Agric. Res. J. Vol. 9, 2009, pp. 17-20  DOI: http://dx.doi.org/10.3126/narj.v9i0.11637